ANALYSIS OF THE DEVELOPMENT OF THE WORLD MONETARY SYSTEM IN THE PERIOD AFTER THE COVID -19 PANDEMIC - Nazaralieva Shohsanam Ilkhom Kizi; Yuldasheva Umida (American Journals, 2023)
The article presents the prospects for the development of the world economy, factors contributing to the transition of the international, regional and national currency systems to a new stage. The basic limitations of the process of development of the global monetary system in post-COVID conditions ( COVID -19 pandemic) are described.
Keywords: currency system, monetary policy, analysis and forecasts, crisis.